Anti-Predator Vigilance as an Indicator of the Costs and Benefits of Supplemental Feeding in Newly Released ‘Alalā (Corvus hawaiiensis) - Lee, Heather N.; Greggor, Alison L.; Masuda, Bryce; Swaisgood, Ronald R. (Frontiers in Conservation Science, 2021)
Although supplemental feeding is commonly used as a conservation strategy during animal translocations, it comes with a number of pros and cons which can be hard to quantify. Providing additional food resources may lead to improved physical health, survivorship, and reproduction. However, offering predictable food sources could make individuals more conspicuous to predators and less aware of their surroundings, disrupting their natural predator-prey dynamic. Decisions such as release cohort size and supplemental feeder design could influence the balance of these costs and benefits, depending on how animals behave in the face of predation risk and static food sources. Additionally, animals released to the wild from long term human care must balance foraging and predation risk while adjusting to a novel environment. To help conservation managers make informed decisions in light of these potential costs, we studied the behavior of a cohort of 11 conservation-bred ‘alalā (Corvus hawaiiensis) at supplemental feeding stations after release into the wild. Vigilance, foraging behavior and social group size was quantified via 1320 trail camera videos of ‘alalā over the span of 12 months. We found that vigilance increased over time since release, suggesting that ‘alalā learn and adjust to their novel surroundings. Both vigilance and eating decreased with group size, indicating that although conspecifics may share the burden of scanning for threats, they also increase competition for food. We also found that the design of the feeder may have limited birds’ abilities to express anti-predator behavior since less vigilance was observed in individuals that manipulated the feeder. Yet, birds may have been able to offset these costs since they increasingly scrounged for food scraps next to the feeder as time progressed. We discuss how changes to behavior over time, social interactions, and feeder design should all be considered when planning supplemental feeding as part of wildlife translocations.